Fullerene C60 supported copper cluster catalyst and application thereof in CO2 electroreduction
By using fullerene C60-supported copper cluster catalyst during electrocatalytic CO2 reduction, the problems of product selectivity and catalyst stability are solved, and efficient CO2 electroreduction to methane is achieved, with good industrial application prospects.
Patent Information
- Application Number
- CN202411615657.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-02-18
AI Technical Summary
There are problems with product selectivity and electrocatalyst stability during electrocatalytic CO2 reduction, resulting in poor selectivity for specific products and unstable catalysts.
Using fullerene C60-supported copper cluster catalyst, nanoscale active sites were obtained through electrochemical reduction of Cu complexes, and metal nanoclusters were anchored through the high electron affinity and uniform large lattice distance of fullerene C60. /Particles, achieve strong electron and constraint effects, and improve the selectivity and stability of the catalyst.
The catalytic selectivity and stability of CO2 electroreduction to methane was significantly improved, and the Faraday efficiency of 55% CH4 product and the current density of 192mAcm-2 were obtained in the flow electrolytic cell, and the Faraday efficiency was maintained at 40% in the stability test of 15000s. .
Smart Images

Figure CN119465268A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a fullerene C 60 The invention relates to a supported copper cluster catalyst and its application in CO2 electroreduction, belonging to the field of new energy CO2 electroreduction catalyst materials. Background Art
[0002] Modern society consumes a large amount of fossil energy (coal, oil, natural gas), and produces a large amount of carbon dioxide (CO2) into the atmosphere, which has caused a series of global climate and environmental problems such as the greenhouse effect. Since the Industrial Revolution, the increasing use of fossil fuels has led to an increase in the concentration of carbon dioxide in the atmosphere. The concentration of carbon dioxide in the global atmosphere has risen from 280ppm in 1750 to 415ppm in 2021, which has led to a series of environmental problems such as global warming and ocean acidification. Excessive carbon dioxide emissions lead to the greenhouse effect, which is the main cause of a series of serious environmental problems such as global warming, sea level rise, and land desertification. Therefore, it is crucial to take measures to reduce the concentration of CO2. Renewable energy such as solar energy, wind energy, and tidal energy can replace traditional fossil fuels and alleviate environmental and energy problems, but large-scale energy storage and transportation problems limit the widespread use of renewable energy. Therefore, it is of great significance to capture and store carbon dioxide and convert it into high-value fuels and chemicals. How to effectively convert and utilize CO2 is one of the most urgent tasks facing mankind. The Paris Agreement, adopted by the United Nations General Assembly in April 2016, proposed a blueprint and vision for global response to climate change and realization of green and low-carbon development after 2020, with the aim of limiting the increase in global average temperature to within 2°C above pre-industrial levels by 2100.
[0003] As an economical, safe and sustainable carbon-oxygen resource compound, CO2 has great development potential in converting it into liquid fuels and chemicals. However, due to the very stable chemical properties of CO2, additional energy needs to be applied to activate and convert it. In actual industrial processes, there are not many reactions that can utilize CO2, such as urea synthesis, carbonate synthesis, methanol synthesis, CO2 reforming of methane, etc. These chemical processes generally require relatively harsh reaction conditions such as high temperature and high pressure, and are high-energy consumption and low-efficiency processes. From the perspective of resource and energy development strategies, using low-grade renewable electricity to efficiently electrochemically reduce CO2 into chemicals or fuels can not only "turn waste into treasure" and reduce CO2 emissions, but also reduce human dependence on fossil fuels, which has important practical significance for alleviating the dual pressures of energy and the environment.
[0004] Electrochemical reduction of CO2 to value-added chemicals and fuels provides a promising approach to address the energy crisis and global warming. CO2 can be converted into C1, C2, or C 2+ Convert carbon dioxide into polycarbons (C2 and C 2+ ) products are more desirable due to their higher value and higher energy density. CO2RR is a highly complex process. By transferring multiple protons and electrons, many different gaseous and liquid products such as formic acid (HCOOH), carbon monoxide (CO), methanol (CH3OH), methane (CH4), ethylene (C2H4) and ethanol (CH3CH2OH) can be obtained, which have similar thermodynamic redox potentials, which leads to poor selectivity for specific products. Therefore, before CO2RR can become a viable option for storing renewable energy, its significant obstacles related to its energy efficiency and selectivity must be overcome.
[0005] Recently, many electrocatalysts have been designed for the reduction of CO2, such as metals, metal oxides, and carbon-based materials. Among these catalysts, copper (Cu) is widely regarded as the most effective catalyst for the electrosynthesis of high value-added products, such as methane, ethylene, ethanol, propanol, and acetate. Among them, hydrocarbons have the highest heat of combustion and provide 24% of the world's energy. The eCO2R-to-CH4 process has become one of the effective ways to close the carbon cycle on a global scale. Copper (Cu) has the ability to reduce CO2 to hydrocarbons, which may be related to the optimal binding energy of CO intermediates on Cu, thereby further reducing CO intermediates. However, the lack of suitable cathode catalysts has hindered the commercial feasibility of eCO2R, which still has low selectivity (<60%), low bias current density (<200mAcm -2 ) and high overpotential of high value-added products, electrochemical reconstruction and other issues, these factors lead to unsatisfactory selectivity and rate for CH4. In order to improve the reduction performance of CO2, people have explored a large number of strategies from multiple aspects such as the composition and structure of the catalyst, the local microenvironment, and the electrode.
[0006] Fullerene (C 60 ) surface due to its high electron affinity (each C 60 The molecules can accept up to 6 electrons), uniform and fluctuating structures with uniform large lattice distances, making them promising catalyst support candidates. These ideal surface properties can achieve strong electronic and confinement effects when anchoring metal nanoclusters / particles.
[0007] So far, there have been a lot of reports on the research work on copper-based catalysts for electrocatalytic CO2RR, and the number of literature is still increasing rapidly every year. However, the reaction selectivity of electrocatalytic CO2RR is still challenging, and there are problems such as electrochemical reconstruction. Therefore, it is still of great significance to study electrocatalysts that are simple to operate and can electro-reduce CO2 to high value-added products. This method can provide a guiding principle for the rational screening and preparation of high-performance CO2RR electrocatalysts. Summary of the invention
[0008] In order to solve the problem of product selectivity and electrocatalyst stability in the electrocatalytic CO2 reduction process, the present invention provides a fullerene C that is easy to synthesize, simple in process, and environmentally friendly for improving the catalytic selectivity and stability of electrocatalytic CO2 reduction to CH4. 60 Preparation method and application of supported copper cluster catalyst. The nanoscale active sites obtained by electrochemical reduction of Cu complexes have excellent electrochemical CO2 reduction selectivity. Fullerene C 60 It has electron affinity, uniform large lattice distance and fluctuating structure, anchors metal nanoclusters / particles, achieves strong electronic and confinement effects, stabilizes the structure and performance of the catalyst, inhibits the reconstruction of nano-copper clusters, and can improve the catalytic performance of the catalyst itself.
[0009] In order to achieve the above-mentioned purpose, the present invention adopts the following technical solutions:
[0010] A fullerene C 60 The preparation method of the supported copper cluster catalyst comprises the following steps:
[0011] Step 1: dissolving CuCl2·2H2O in methanol by ultrasonication to form solution A, and dissolving 1,10-phenanthroline monohydrate in methanol by ultrasonication to form solution B; mixing solution B with solution A and reacting by ultrasonication to obtain a Cu-N complex solution;
[0012] Step 2: stirring and mixing the Cu-N complex solution and the KHCO3 solution to obtain a precursor solution;
[0013] Step 3: Fullerene C 60 The powder was ultrasonically dispersed in ethanol, then sprayed on the surface of carbon paper and dried to obtain the loaded C 60 Carbon paper;
[0014] Step 4: Prepare the load C in step 3 60 The carbon paper was used as the working electrode, and the precursor solution prepared in step 2 was used as the electrolyte. Electrochemical reduction was performed in a three-electrode electrolytic cell to load the copper clusters on the fullerene C 60 surface; take out the electrode and dry it in vacuum to obtain fullerene C for CO2 electroreduction 60Supported copper cluster catalyst.
[0015] Furthermore, in step 1, the mass concentration of CuCl2·2H2O in solution A is 70-90 mg / mL, the mass concentration of 1,10-phenanthroline monohydrate in solution B is 250-300 mg / mL, and the volume ratio of solution A to solution B is 1-3:2.
[0016] Furthermore, in step 1, the ultrasonic reaction is carried out for 1 to 3 hours at room temperature.
[0017] Furthermore, in step 2, the concentration of the KHCO3 solution is 25-75 mg / mL, and the volume ratio of the Cu-N complex solution to the KHCO3 solution is 1:5-20.
[0018] Furthermore, in step 2, the stirring time is 2-10 min and is carried out at room temperature.
[0019] Furthermore, the electrochemical reduction time is 300-1800s.
[0020] Furthermore, the counter electrode for electrochemical reduction is a graphite carbon rod, and the reference electrode is an Ag / AgCl electrode.
[0021] The fullerene C prepared by the above preparation method of the present invention 60 Cu element accounts for 2.3% of C in the supported copper cluster catalyst. 60 The catalyst has a mass content of 0.5-1wt%, and can be used in the electrochemical reduction reaction of CO2 in a neutral or alkaline environment.
[0022] The beneficial effects of the present invention are embodied in:
[0023] 1. The present invention electrochemically reduces the complex formed by Cu ions and 1,10-phenanthroline monohydrate in the solution to form copper cluster active sites and load them on fullerene C 60 Surface. Due to C 60 The high electron affinity (each C 60 The molecules can accept up to 6 electrons), uniform large lattice distance and fluctuating structure enable it to achieve strong electronic and confinement effects when anchoring clusters, improving the selectivity and stability of copper cluster electrochemical CO2 reduction to methane products.
[0024] 2. Fullerene C obtained by the present invention 60 The supported copper cluster catalyst exhibited excellent methane selectivity and stability in H-type electrolytic cells and flow electrolytic cells. The test results in the flow electrolytic cell showed that the fullerene C 60 The nanoscale copper cluster catalyst achieves a CH4 product Faraday efficiency of 55% and a CH4 current density of 192 mA cm-2 , and after 15000s stability test, the CH4 product Faraday efficiency can still reach 40%, indicating that it has long-term operation capability and good stability.
[0025] 3. The catalyst obtained by the present invention exhibits an integral structure and can be directly tested when used as a working electrode. The preparation process is simple and convenient for large-scale preparation and production. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The Cu-C obtained in Example 1 60 Transmission electron microscopy image of the catalyst.
[0027] Figure 2 The Cu-C obtained in Example 1 60 Double spherical aberration-corrected high-angle annular dark-field scanning transmission electron microscopy image of the catalyst.
[0028] Figure 3 The Cu-C obtained in Example 1 60 Elemental analysis results of catalysts.
[0029] Figure 4 The Cu-C obtained in Example 1 60 XRD analysis results of the catalyst.
[0030] Figure 5 The Cu-C obtained in Example 1 60 Performance test results of the catalyst for catalytic CO2 reduction in an H-type electrolytic cell;
[0031] Figure 6 The Cu-C obtained in Example 1 60 Performance test results of the catalyst for catalytic CO2 reduction in a flow electrolytic cell;
[0032] Figure 7 The Cu obtained in Example 2 0.5 -C 60 Performance test results of the catalyst for catalytic CO2 reduction in an H-type electrolytic cell;
[0033] Figure 8 The Cu obtained in Example 3 1.5 -C 60 Performance test results of the catalyst for catalytic CO2 reduction in an H-type electrolytic cell;
[0034] Fig. 9 The Cu-C obtained in Example 4 60 -Performance test results of 1800S catalyst for catalytic CO2 reduction in flow electrolysis cells;
[0035] Fig.10 The performance test results of the Cu-CB catalyst obtained in Example 5 in the flow electrolysis cell for catalytic CO2 reduction;
[0036] Fig.11 The CuCl2-C obtained in Example 6 60 Performance test results of the catalyst for catalytic CO2 reduction in a flow electrolytic cell;
[0037] Fig.12 The pure C obtained in Example 7 60 Performance test results of the catalyst for catalytic CO2 reduction in a flow electrolytic cell;
[0038] Fig.13 The Cu-C obtained in Example 8 60 Performance test results of the catalyst for catalytic CO2 reduction in an H-type electrolytic cell. DETAILED DESCRIPTION
[0039] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the present invention is further described below in conjunction with specific embodiments. If no specific technology or conditions are specified in the embodiments, they can be carried out according to the technology or conditions described in the literature in the field or according to the product manual.
[0040] Example 1
[0041] In this example, fullerene C was prepared according to the following steps. 60 Supported copper cluster catalyst:
[0042] Step 1: 80 mg of CuCl2·2H2O was ultrasonically dissolved in 1 mL of methanol to form solution A. 560 mg of 1,10-phenanthroline monohydrate was ultrasonically dissolved in 2 mL of methanol to form solution B. Solution B was quickly mixed with solution A and ultrasonicated for 1 h to obtain a Cu-N complex solution.
[0043] Step 2: Mix 1 mL of the Cu-N complex solution with 30 mL of a 50 mg / mL KHCO3 solution and stir for 2 min to make it evenly distributed to obtain a precursor solution.
[0044] Step 3: 6 mg of fullerene C 60 Ultrasonic dispersion in 1 mL of ethanol to prepare a slurry, which was then sprayed on the surface of carbon paper and dried. The spraying area was 1*1 cm 2 , Fullerene C 60 The loading on the carbon paper surface is 0.5 mg / cm 2 .
[0045] Step 4: Prepare the load C in step 3 60The carbon paper was used as the working electrode, the precursor solution prepared in step 2 was used as the electrolyte, the graphite carbon rod was used as the counter electrode, and the Ag / AgCl electrode was used as the reference electrode. The electrochemical reduction was carried out in a three-electrode electrolytic cell for 600 s to load the copper clusters on the fullerene C 60 surface; take out the electrode and dry it in vacuum to obtain fullerene C for CO2 electroreduction 60 Supported copper cluster catalyst, denoted as Cu-C 60 catalyst.
[0046] Figure 1 The Cu-C prepared in this example 60 Transmission electron microscopy (TEM) images of the catalyst. Figure 2 The Cu-C prepared in this example 60 The AC HAADF-STEM image of the catalyst shows that the copper clusters obtained after electroreduction are attached to the C 60 The copper clusters were densely enriched amorphous clusters of about 2-3 nm, and no metal-related nanoclusters or nanoparticles with lattice were detected.
[0047] Figure 3 The Cu-C prepared in this example 60 From the XPS graph of the catalyst, it can be seen that the Cu in the reduced product is low-valent.
[0048] Figure 4 The Cu-C prepared in this example 60 From the XRD pattern of the catalyst, it can be seen that there is no crystalline diffraction peak of Cu in the obtained product, proving that it has an amorphous structure, which is consistent with the transmission electron microscopy results.
[0049] The Cu-C obtained in this example was verified by the following steps. 60 Catalyst performance in CO2 electroreduction:
[0050] 1. H-type electrolytic cell: On an electrochemical workstation (CHI 6081E, Shanghai CH Instruments Co., China), a double-chamber hydrogen cell separated by an ion exchange membrane (Nafion 117) was used, and three electrodes: working electrode, graphite carbon rod electrode and Ag / AgCl (saturated KCl) reference electrode were used for linear sweep voltammetry (LSV) measurement and constant voltage test. In the experiment, 0.5M KHCO3 solution was injected into the anode cell and cathode cell respectively. In all measurements, Ag / AgCl was used as the reference electrode, and the potential (vs. Ag / AgCl) was converted to RHE using the following formula: E RHE =E Ag / AgCl +E θAg / AgCl +0.0591pH E θ Ag / AgCl =0.197 (saturated KCl).
[0051] Before testing, the cathode electrolyte was bubbled with CO2 for 30 min to remove air and obtain a CO2 saturated solution. The reaction was carried out at a constant potential and a stable CO2 flow rate (20 mL / min). Micromagnetic stirring was used to obtain a uniform electrolyte. Before testing, the cathode was electrochemically reduced using cyclic voltammetry at a scan rate of 0.01 V s -1 In the case of , 10 cycles were performed in the range of 0 to −1.4 V (vs. RHE) until stabilization to remove possible oxidative species.
[0052] 2. Flow electrolysis cell: High purity CO2 (99.999%) gas continuously passes through the flow chamber behind the GDL and diffuses into the electrolyte at the catalyst. During the measurement, CO2 gas directly enters the cathode GDL at a rate of 30 mL / min.
[0053] The cathode electrolyte (1M KOH) flow rate was controlled by a peristaltic pump at 30 rpm. The anode chamber and cathode chamber were separated by an anion exchange membrane. Ag / AgCl electrode and nickel foam were used as reference electrode and counter electrode, respectively. The linear sweep voltammetry (LSV) curve was used to select the appropriate potential range of the catalyst and perform constant current testing. In all measurements, Ag / AgCl was used as the reference electrode, and the potential (vs. Ag / AgCl) was converted to RHE using the following formula: E RHE =E Ag / AgCl +E θ Ag / AgCl +0.0591pH E θ Ag / AgCl =0.197 (saturated KCl).
[0054] Figure 5 and Figure 6 The Cu-C 60 The performance test results of the catalyst for catalytic CO2 reduction in H-type electrolyzers and flow electrolyzers. It can be seen that the selectivity of the catalyst for CO2 electroreduction to methane can reach 42% in H-type electrolyzers and 55% in flow electrolyzers, showing excellent performance in electroreducing CO2 to high value-added products.
[0055] Example 2
[0056] In this example, fullerene C was prepared in the same manner as in Example 1. 60 The only difference is that the amount of Cu-N complex solution in step 2 is 0.5 mL, and the obtained product is recorded as Cu 0.5-C 60 catalyst.
[0057] Figure 7 The Cu obtained in this example 0.5 -C 60 The performance test results of the catalyst for catalytic CO2 reduction in an H-type electrolytic cell. It can be seen that compared with Example 1, after reducing the concentration of the metal complex in this example, the number of active sites obtained by reduction is reduced, and the selectivity of the methane product is reduced.
[0058] Example 3
[0059] In this example, fullerene C was prepared in the same manner as in Example 1. 60 The only difference is that the amount of Cu-N complex solution in step 2 is 1.5 mL, and the obtained product is recorded as Cu 1.5 -C 60 catalyst.
[0060] Figure 8 The Cu obtained in this example 0.5 -C 60 Performance test results of the catalyst for catalytic CO2 reduction in an H-type electrolytic cell. It can be seen that compared with Example 1, after increasing the concentration of the metal complex in this example, the number of active sites obtained by reduction increased, but the selectivity of the methane product remained basically unchanged, proving that as the number of active sites increased, the active sites involved in the reaction did not change much.
[0061] Example 4
[0062] In this example, fullerene C was prepared in the same manner as in Example 1. 60 The supported copper cluster catalyst is different from the electrochemical reduction time in step 4, which is 1800 s. The obtained product is recorded as Cu-C 60 -1800s Catalyst.
[0063] Fig. 9 The Cu-C 60 -1800s catalyst performance test results for catalytic CO2 reduction in a flow electrolyzer. It can be seen that compared with Example 1, the selectivity of ethylene products increased and the selectivity of methane products decreased, proving that the reaction active sites changed with the increase of electroreduction time.
[0064] Example 5
[0065] In this example, the carbon black supported copper cluster catalyst was prepared in the same manner as in Example 1, except that the fullerene C in step 3 was replaced by 60 The Cu-CB catalyst was replaced with an equal amount of carbon black.
[0066] Fig.10 The performance test results of the Cu-CB catalyst obtained in this example for catalytic CO2 reduction in a flow electrolytic cell are shown in Figure 1. Compared with Example 1, the selectivity of hydrogen product increased and the selectivity of methane product decreased, which proves that the fullerene C 60 A confinement effect was achieved when anchoring copper clusters, improving the selectivity of electrochemical CO2 reduction to methane products.
[0067] Example 6
[0068] In this example, fullerene C was prepared according to the following steps. 60 Supported copper catalyst:
[0069] Step 1: 80 mg of CuCl2·2H2O was dissolved in 1 mL of methanol by ultrasonication to form solution A.
[0070] Step 2: Mix 1 mL of solution A with 30 mL of 50 mg / mL KHCO3 solution and stir for 2 min to make it evenly distributed to obtain a precursor solution.
[0071] Step 3: Same as Example 1.
[0072] Step 4: Same as Example 1.
[0073] The catalyst obtained in this example is denoted as CuCl2-C 60 catalyst.
[0074] Fig.11 The CuCl2-C 60 Performance test results of the catalyst for catalytic CO2 reduction in a flow electrolytic cell. It can be seen that compared with Example 1, when the copper complex solution is replaced by pure Cu solution, the active sites obtained by reduction are changed, the selectivity of ethylene product is significantly improved, and the selectivity of methane product is sharply reduced. This shows that the metal complex plays a decisive role in the generation of active sites during the electroreduction process, and the synthesis of copper clusters is regulated by metal complex reduction.
[0075] Example 7
[0076] In this example, the load C prepared in step 3 of Example 1 60 The carbon paper was directly used as catalyst (denoted as C 60 catalyst).
[0077] Fig.12 C obtained in this example 60 The performance test results of the catalyst for catalytic CO2 reduction in a flow electrolytic cell. It can be seen that compared with Example 1, when the metal complex precursor is lost, the CO2 electroreduction active sites disappear, and the fullerene C 60The selectivity of the products obtained on the electro-reduction catalyst changes, and the selectivity of hydrogen products can reach 100%, without any CO2 reduction products. 60 It does not have the performance of electrochemical CO2 reduction, and the copper clusters obtained by electroreduction of the metal complex are active sites for CO2 electroreduction.
[0078] Example 8
[0079] This example verifies the Cu-C obtained in Example 1. 60 Stability of the catalyst: The H cell test method of Example 1 was followed, except that the constant voltage stability test voltage was -1.4 V (vs RHE).
[0080] The Cu-C 60 Catalytic stability of the catalyst Fig.13 In the H-type electrolytic cell, under the voltage of -1.4V, the methane product selectivity can reach 40%, and the durability can reach 15000s, indicating that it has long-term operation capability and good stability.
[0081] In summary, the Cu-C 60 The electrocatalyst is a fullerene C 60 The invention discloses a method for preparing a supported copper cluster CO2 electroreduction catalyst, wherein the copper-o-phenanthroline complex is reduced by an electroreduction method to prepare a copper cluster active site having a high efficiency of reducing CO2 to methane. 60 The catalyst has good selectivity for methane production and due to the fullerene C 60 Has high electron affinity (each C 60 The molecules can accept up to 6 electrons), uniform large lattice distance and fluctuating structure can achieve strong electronic and confinement effects when anchoring metal nanoclusters / particles. 60 The supported copper cluster catalyst improves the selectivity and stability of electrochemical CO2 reduction to methane products.
[0082] The fullerene C disclosed in the present invention 60 The loaded copper cluster catalyst has a simple and convenient preparation method, is green and environmentally friendly, is easy to produce on a large scale for catalyst electrodes, and has good prospects for industrial application.
Claims
1. A fullerene C 60 The method for preparing a supported copper cluster catalyst is characterized in that: The steps include: Step 1: dissolving CuCl2·2H2O in methanol by ultrasonication to form solution A, and dissolving 1,10-phenanthroline monohydrate in methanol by ultrasonication to form solution B; mixing solution B with solution A and reacting by ultrasonication to obtain a Cu-N complex solution; Step 2: stirring and mixing the Cu-N complex solution and the KHCO3 solution to obtain a precursor solution; Step 3: Fullerene C 60 The powder was ultrasonically dispersed in ethanol, then sprayed on the surface of carbon paper and dried to obtain the loaded C 60 Carbon paper; Step 4: Prepare the load C in step 3 60 The carbon paper was used as the working electrode, and the precursor solution prepared in step 2 was used as the electrolyte. Electrochemical reduction was performed in a three-electrode electrolytic cell to load the copper clusters on the fullerene C 60 surface; take out the electrode and dry it in vacuum to obtain fullerene C for CO2 electroreduction 60 Supported copper cluster catalyst.
2. A fullerene C according to claim 1 60 The method for preparing a supported copper cluster catalyst is characterized in that: In step 1, the mass concentration of CuCl2·2H2O in solution A is 70-90 mg / mL, the mass concentration of 1,10-phenanthroline monohydrate in solution B is 250-300 mg / mL, and the volume ratio of solution A to solution B is 1-3:
2.
3. A fullerene C according to claim 1 60 The preparation method of the supported copper cluster CO2 electro-reduction catalyst is characterized in that: In step 1, the ultrasonic reaction is carried out for 1 to 3 hours at room temperature.
4. A fullerene C according to claim 1 60 The method for preparing a supported copper cluster catalyst is characterized in that: In step 2, the concentration of the KHCO3 solution is 25-75 mg / mL, and the volume ratio of the Cu-N complex solution to the KHCO3 solution is 1:5-20.
5. A fullerene C according to claim 1 60 The method for preparing a supported copper cluster catalyst is characterized in that: In step 2, the stirring time is 2-10 min and the stirring is carried out at room temperature.
6. A fullerene C according to claim 1 60 The method for preparing a supported copper cluster catalyst is characterized in that: In step 3, fullerene C 60 The loading amount on the carbon paper surface is 0.5~1.5mg / cm 2 .
7. A fullerene C according to claim 1 60 The method for preparing a supported copper cluster catalyst is characterized in that: In step 4, the electrochemical reduction time is 300-1800s.
8. A fullerene C according to claim 1 60 The method for preparing a supported copper cluster catalyst is characterized in that: In step 4, the counter electrode for electrochemical reduction is a graphite carbon rod, and the reference electrode is an Ag / AgCl electrode.
9. A fullerene C obtained by the preparation method according to any one of claims 1 to 8 60 Supported copper cluster catalyst.
10. A fullerene C as claimed in claim 9 60 Application of supported copper cluster catalysts in CO2 electrochemical reduction reaction under neutral or alkaline environment.
Citation Information
Cited By
Preparation method of electro-catalytic material Cu-MOF-coated C70NT for carbon dioxide reduction
CN120625098A